PERENCANAAN DINDING PENAHAN TANAH UNTUK JALUR IRIGASI - Syekhan Aria Putu Siradz; Rulhendri Rulhendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2023)
Landslides that occur in the area, where every landslide event always poses no small danger. Jampang Tengah is one of the sub-districts located in Sukabumi Regency which has interesting landscape conditions to study regarding the potential for landslide disasters. The Central Jampang area has a steep sedimentary hill morphology. The geology of this area is dominated by sandstone, breccia, limestone lithology and is influenced by geological structures such as the Walat fault and the Cimandiri fault. Basically, Jampang Tengah is an agrarian area, where the majority of people are farmers. The purpose of this paper is to analyze by considering the need for environmentally friendly concrete retaining structures in order to obtain a minimum cost. To identify eco-friendly and cost-effective designs.